Effect of spiral scanning laser power on arc thermal field in double pulsed CMT - Gang ZHANG; Zhongyi LIU; Xu MENG; Yu SHI; Ding FAN (Hanjie xuebao)
To study the effect of spiral scanning laser power on the arc thermal field, droplet transfer, and porosity defects in double pulsed cold metal transfer (CMT) additive manufacturing of aluminum alloy, comparative experiments of laser arc additive manufacturing with variable power were conducted. The infrared thermography, spectral measurement, and high-speed imaging technology were used to analyze the radial temperature field distribution of the arc near the molten pool surface, the plasma behavior of the intersection region, the droplet transition, and the porosity defects when the scanning laser was introduced. The results indicate that the radial temperature field of the arc near the molten pool surface exhibits significant fluctuations and a steep temperature gradient with low arc stability in the double pulsed CMT. When the laser power is set to 600–1200 W, the radial temperature distribution of arc becomes more uniform, and the temperature gradient significantly decreases; the arc temperature near the molten pool surface is notably elevated (a maximum increase of 900 ℃), which promotes the ionization of Mg and Al atoms, resulting in more generation of Mg II, Mg III, Al II, and Al III ions, and improving the arc stability. At laser power of 600 W and 1200 W, the electron density increases by 6% and 17%, and the electron temperature rises by 400 K and 800 K. The laser metal vapor effectively reduces the droplet transfer frequency, lessens the droplet impact on the molten pool, and contributes to greater stability. The number of pores in the components decreases significantly, with their distribution becoming more dispersed; at a laser power of 1200 W, the porosity is almost eliminated.